2000
DOI: 10.1016/s0735-1097(00)01025-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with congestive heart failure treated with standard versus high doses of enalapril: a multicenter study

Abstract: No significant differences were found in survival and clinical and hemodynamic variables between patients receiving standard and those receiving high doses of enalapril.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Other studies have compared low-and high-dose ACE-inhibitors but are substantially limited compared to ATLAS and NETWORK in terms of statistical power to assess mortality and outcome. [30][31][32] Overall, these trials demonstrate a potential advantage of higher doses in terms of improved symptoms and reduced frequency of hospitalizations, but do not provide conclusive proof that higher doses improve survival. These results may have led to less aggressive recommendations and guidelines regarding titration of ACE-inhibitors and ARBs in HF patients as compared to b-blockers.…”
Section: Target Doses Of Ace-inhibitors and Angiotensin Receptor Blocmentioning
confidence: 90%
“…Other studies have compared low-and high-dose ACE-inhibitors but are substantially limited compared to ATLAS and NETWORK in terms of statistical power to assess mortality and outcome. [30][31][32] Overall, these trials demonstrate a potential advantage of higher doses in terms of improved symptoms and reduced frequency of hospitalizations, but do not provide conclusive proof that higher doses improve survival. These results may have led to less aggressive recommendations and guidelines regarding titration of ACE-inhibitors and ARBs in HF patients as compared to b-blockers.…”
Section: Target Doses Of Ace-inhibitors and Angiotensin Receptor Blocmentioning
confidence: 90%
“…The main clinical studies are summarized in Table II. Absence of dose-dependency was noted by Nanas et al, 32 where standard and high doses of enalapril were compared. This trial addressed whether doses above those studied in the landmark trials were superior.…”
Section: Clinical Outcomesmentioning
confidence: 90%
“…The two exceptions include Nanas et al, 32 which concluded that doses higher than recommended did not have any added benefit, and the NETWORK trial, 35 which might not have been powered to detect a difference in dosing outcomes, as it had fewer patients and shorter duration of follow-up compared with the ATLAS study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of enalapril at different doses (up to 2, 5, 20, and 60 mg) was investigated in two of these studies, and no significant difference was observed (15,16). As for the ATLAS study, low-dose lisinopril (2.5-5 mg) was compared with high-dose lisinopril (32.5-35 mg).…”
Section: Introductionmentioning
confidence: 99%